Developmental Expression Pattern of the Piwi1 Gene, Timing of Sex Differentiation and Maturation in Artificially Produced Juvenile Boring Giant Clam, Tridacna crocea - Zhou, Yinyin; Li, Yunqing; Liao, Qingliang; Shi, Gongpengyang; Qin, Yanpin; Zhang, Yuehuan; Ma, Haitao; Li, Jun; Yu, Ziniu (Frontiers in Marine Science, 2022)
P-element-induced wimpy testis (Piwi) is a key gene involved in germ cell development in a diverse range of organisms. However, in giant clams, the function of Piwi remains unclear. In the present study, we isolated the full-length cDNA of Piwi ortholog (Tc-Piwi1) and analyzed its expression patterns in the gonads of adult and juvenile Tridacna crocea. The results of qPCR showed that the transcript of Tc-Piwi1 was mainly expressed in gonad tissue. In addition, the relative expression level of Tc-Piwi1 increased with the proliferation of male and female germ cells during the adult gonad development stage, suggesting that Tc-Piwi1 might be involved in gametogenesis. In situ hybridization revealed that Tc-Piwi1 RNA was located in female and male germ cells and strongly expressed in male germ cells in the early stage. Furthermore, immunohistochemical experiments further confirmed that Tc-Piwi1 was mainly located in primordial germ cells (PGCs), germ stem cells (GSCs), and female and male germ cells of early development, so it could be used as a marker gene of T. crocea germ cells. Whole-mount in situ hybridization suggested that Tc-Piwi1 was of maternal origin and located in two clusters of cells in the trochophore-larvae stage, implying that these cells might be putative PGCs during the embryo development. Finally, Tc-Piwi1 was used as a molecular marker to elucidate the gonadal formation, sex differentiation, and gonadal maturation process of juvenile T. crocea for the first time in the Tridacna family. Collectively, all these results revealed that Tc-Piwi1 was involved in germline formation and sex differentiation in T. crocea.